2014
DOI: 10.1002/2013jd020207
|View full text |Cite
|
Sign up to set email alerts
|

Optical constants for Asian dust in midinfrared region

Abstract: Asian dust aerosols are composed of quartz, plagioclase, K-feldspar, calcite, and phyllosilicates. The optical constants for mixtures of these minerals are important not only to understand the effects of Asian dust on climate but also to retrieve the properties of Asian dust. In this work, the optical constants for labradorite and orthoclase, representative minerals of plagioclase and K-feldspar, respectively, are determined for the spectral range of 500-2000 cm À1 using bidirectional reflectance data from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The spectral dependence of (a) the real and (b) the imaginary parts of the complex refractive index for different mineral compositions. Illite data are from Querry et al (1978), quartz from Peterson and Weinman (1969), kaolinite and montmorillonite from Glotch et al (2007), calcite from Querry et al (1978) and Long et al (1993), gypsum from Long et al (1993), hematite from Marra et al (2005), and feldspar (labradorite) from Lee and Park (2014). No data are available for the imaginary part of feldspar.…”
Section: The Dust Emission Modulementioning
confidence: 99%
“…The spectral dependence of (a) the real and (b) the imaginary parts of the complex refractive index for different mineral compositions. Illite data are from Querry et al (1978), quartz from Peterson and Weinman (1969), kaolinite and montmorillonite from Glotch et al (2007), calcite from Querry et al (1978) and Long et al (1993), gypsum from Long et al (1993), hematite from Marra et al (2005), and feldspar (labradorite) from Lee and Park (2014). No data are available for the imaginary part of feldspar.…”
Section: The Dust Emission Modulementioning
confidence: 99%
“…An earlier study by Lee and Park () already reported the optical constants for AD in the midinfrared region. Thus, the present study provides extended spectral coverage of the optical constants for AD.…”
Section: Introductionmentioning
confidence: 94%
“…The Absorbing Ångström Exponent (AAE), which represents the wavelength dependence of particle absorption, differs significantly between dust and the other two types in the 440-675 nm wavelength range. At shorter wavelengths, spectral variations of the imaginary part of the refractive index for the HAF and dust types are assumed based on Kirchstetter et al [39] and Lee et al [40], respectively. Kirchstetter et al [39] showed that the imaginary index for brown carbon varies following a power law in the UV range.…”
Section: Aerosol Model Assumptionsmentioning
confidence: 99%
“…Lee et al [40] obtained the spectral variation from 0.2 to 1.0 µm by assuming transported Asian dust consists of internally mixed mineral components and showed that the imaginary index varies more slowly between 350 and 500 nm than indicated by the Optical Properties of Aerosols and Clouds (OPAC) 'mineral-transported' dataset [41]. Using the results of Lee et al [40], the ω for dust was obtained as 1.835. This ω value is generally lower than the values of the Saharan dust sample described by Wagner et al [42].…”
Section: Aerosol Model Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation